TUNTUTAN HAK-HAK SUAMI PASCA PERCERAIAN: KAJIAN DI MAHKAMAH SYARIAH KOTA BHARU, KELANTAN: Husband’s Claims Over Divorce Rights: A Study at Kota Bharu Shariah Court, Kelantan - Nik Ibrahim, Nik Nur Athirah; Mat Hussin, Mohd Norhusairi (Journal of Shariah Law Research, 2017)
As we all known, there are some legal rights that had been given and obtained by husband after divorce. The research is focused on the claim of these rights in Kota Bharu Shariah Court, Kelantan as enacted in Islamic Family Law Enactment No. 6 of Kelantan in 2002. Among the provided claims are matrimonial property (harta sepencarian) and child custody right (ḥaḍānah). It is focused on cases from 2013 until 2015 by referring to the statistics of claims initiated by husband and the rights that are successfully acquired. The outcomes show that only 6 over 40 cases of claim for matrimonial property right throughout the past three years were initiated by husband. Meanwhile, claims for child custody only 25 out of 72 cases were initiated by husband. The pattern of husband’s claims over divorce rights each year are inconsistent and without positive rise compared to the claims initiated by wife.